Elevated Plasma Factor IXa Activity in Premenopausal Women on Hormonal Contraception - Tanratana, P.; Ellery, Paul; Westmark, P.; Mast, A.; Sheehan, J. (Lippincott Williams & Wilkins, 2018)
Objective - Combined oral contraceptives induce a reversible hypercoagulable state with an enhanced risk of venous thromboembolism, but the underlying mechanism(s) remain unclear. Subjects on combined oral contraceptives also demonstrate a characteristic resistance to APC (activated protein C) in the thrombin generation assay. Here, we report the potential role of plasma factor IXa (FIXa) as a mechanism for hormone-induced systemic hypercoagulability. Approach and Results - A novel assay was used to determine FIXa activity in plasma samples from volunteer blood donors. Plasma from 36 premenopausal females on hormonal contraception and 35 not on hormonal contraception, 35 postmenopausal females, and 10 males were analyzed for FIXa activity, total PS (protein S), total tissue factor pathway inhibitor (TFPI), and TFPI-a antigen. Premenopausal females on hormonal contraception demonstrated significantly increased FIXa activity and decreased TFPI-a compared with the other groups. Remarkably, FIXa values were not normally distributed in the hormonal contraception group, but skewed toward the high end. Plasma FIXa activity inversely correlated with both TFPI-a and total PS antigen. Ex vivo determination of TF-dependent FIX activation in FV-deficient plasma demonstrated that inhibitory anti-TFPI antibodies enhanced FIXa generation by 2- to 3-fold, whereas addition of 75 nmol/L PS reduced FIXa generation by ˜2-fold. Further, increasing FIXa concentration enhanced APC resistance during TF-triggered plasma thrombin generation. Conclusions - Elevation of plasma FIXa activity in association with reductions in TFPI-a and PS is a potential mechanism for systemic hypercoagulability and resistance to APC in premenopausal females on hormonal contraception.